1995
DOI: 10.1210/mend.9.1.7539107
|View full text |Cite
|
Sign up to set email alerts
|

Fusing the carboxy-terminal peptide of the chorionic gonadotropin (CG) beta-subunit to the common alpha-subunit: retention of O-linked glycosylation and enhanced in vivo bioactivity of chimeric human CG.

Abstract: The hCG beta-subunit contains a carboxy-terminal extension bearing four serine-linked oligosaccharides [carboxy-terminal peptide (CTP)], which is important for maintaining its longer half-life compared with the other glycoprotein hormones. Previously, we enhanced the in vivo half-life of FSH by fusing the CTP to the carboxy end of FSH beta coding sequence. The alpha-subunit is common to the glycoprotein family. We constructed alpha-subunit CTP chimeras, since such analogs with the appropriate O-linked glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 7 publications
3
36
2
Order By: Relevance
“…This shows that the additional peptide portion does not interfere either with the combination of subunits or with the association of the so-formed dimer with the LH receptor. These data contrast with those of Furuhashi et al (11) who produced an hCG chimera with an additional b carboxyterminal peptide (hCGb-CTP) fused to the Cterminus of the a-subunit. This elongated a-subunit (ha-CTP) recombined efficiently with wild-type hCGbsubunit but the so-formed dimer exhibited very low binding activity to the human LH receptor expressed in the human fetal kidney 293 cell line (<5% relative to wild-type hCG).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This shows that the additional peptide portion does not interfere either with the combination of subunits or with the association of the so-formed dimer with the LH receptor. These data contrast with those of Furuhashi et al (11) who produced an hCG chimera with an additional b carboxyterminal peptide (hCGb-CTP) fused to the Cterminus of the a-subunit. This elongated a-subunit (ha-CTP) recombined efficiently with wild-type hCGbsubunit but the so-formed dimer exhibited very low binding activity to the human LH receptor expressed in the human fetal kidney 293 cell line (<5% relative to wild-type hCG).…”
Section: Discussioncontrasting
confidence: 88%
“…Thus, the +24 peptide does not exert any inhibitory activity on hCG binding to rat LH receptors when present at the C-terminus of the a-subunit. This extension is only slightly shorter than the b-CTP (28 amino acid residues) but the latter is known to bear Osaccharide chains on four of its eight serine residues (Ser 121, 127, 132, 138 ) in the natural hCG molecule (12) and was also found to be O-glycosylated when fused to the C-terminus of the ha-subunit (11). Multiple Oglycosylation in segments of proteins impedes the folding of these regions, leading to bulky extended flexible structures (13).…”
Section: Discussionmentioning
confidence: 99%
“…This may permit the appropriate interactions between the subunits. In addition, previous studies showed that ligation of the CTP to hFSH␤ (13), hTSH␤ (14), or hCG␣ (15) did not significantly affect assembly or in vitro biological activity, but was important for the in vivo potency of the chimeras.…”
Section: Thyrotropin (Tsh)mentioning
confidence: 96%
“…Fusion of peptides to this portion of the ␣-subunit has been shown to have varying effects on hormone activity (20,21). Therefore, when we began these studies we were concerned that the presence of a crosslink between the ␣CT and the hCG ␤-subunit might destroy heterodimer activity by a mechanism that was unrelated to the ability of this portion of the hormone to contact the LHR.…”
Section: Resultsmentioning
confidence: 99%